A Dissident of Paradise. The Radical Heterodox Condition of Writing of Lois Pereiro - Martínez Teixeiro, Alva (Madrygal. Revista de Estudios Gallegos, 2017)
This article, on the one hand, addresses the original work of Lois Pereiro and presents an analysis, from a unifying –but not a simplistic– point of view, of this heterogeneous and complex corpus as a deviation when compared to contemporary literary canons. On the other hand, aims to reflect from a holistic perspective on some aspects of this entire literary work, in which we can summarize both the renewing character and the different levels of complexity resulting from his exemplary investigation of human nature.
Keywords: Lois Pereiro; Subjectivity; Elimination; Isolation; Critical Reason.